English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Questions refer to the following functions: f(x) = 3x-5 and g(x) = -x2 + 1.
3. Find f(3) * g(2).


A.
-20

B.
-12

C.
12

D.
20

4. 1/5g(6)


A.
-8

B.
-7 2/5

C.
-7

D.
-6 4/5

2007-06-12 14:03:49 · 8 answers · asked by sunny 1 in Science & Mathematics Mathematics

8 answers

f(3) = 3*3-5 = 4
g(2) = -2^2 +1 = -3

f(3)*g(2) = 4*-3 = -12


So, B.
I'm assuming that what you meant was g(x) = -x^2 + 1.

In which case for the second part, g(6) = -6^2 +1 = -36+1 = -35.
(1/5)(-35) = -7.

So, C.

2007-06-12 14:07:02 · answer #1 · answered by ya_tusik 3 · 0 0

f(x) means evaluate the function, f, at the value of x. An easier way to think of this, or at least a way that may be more familiar, is that f(x) = y. So, you have two functions/equations:
f(x) = y1 = 3x - 5
g(x) = y1 = -x^2 +1

A quick note: -x^2 means you square x first, then take the negative. (-x)^2 means you take the negative of x, then you square it.

3. f(3)*g(2) means you should evaluate the first function (f, or y1) at 3 and multiply it by what you get when you plug 2 into the second function (g or y2).
f(3) = 3(3) - 5 = 4
g(2) = -2^2 + 1 = -3
f(3)*g(2) = 4(-3) = -12

4. Not sure what you mean on this one. Is it 1/[5*g(2)], or is it (1/5)*g(6)? Either way, find g(6) in the same way you evaluated the ones above, then plug it in to the correct formula.

2007-06-12 21:14:09 · answer #2 · answered by Sci Fi Insomniac 6 · 1 0

f(x) = 3x-5, g(x) = -x^2 + 1.

Q3.
f(3) = 3(3) - 5 = 9-5 = 4
g(2) = -2^2 + 1 = -4 + 1 = -3.
So f(3) × g(2) = 4 × (-3) = -12.
So answer B is correct.

Q4.
g(6) = -6^2 + 1 = -36 + 1 = -35.
So (1/5) g(6) = (1/5)(-35) = -7.
So answer C is correct.

2007-06-12 21:08:21 · answer #3 · answered by Scarlet Manuka 7 · 0 0

3 has been answered.

For (4), 6^2 = 36. So -36+1 = -35.
Take 1/5 of this, so we divide -35 by 5, we get -7.
S the answer is C.

2007-06-12 21:12:22 · answer #4 · answered by tsr21 6 · 0 0

3. f(3) * g(2) = (3*3 - 5) * [-(2^2) + 1]
= (9-5)*(-4+1)
=4 * -3 = -12 choice B

4. I Assume you mean (1/5) g(6)
= (1/5) [-(6^2) + 1]
= (1/5) * -35 = -7 choice C

2007-06-12 21:09:34 · answer #5 · answered by MathProf 4 · 0 0

f(x) = 3x-5 and g(x) = -x2 + 1.
f(3) * g(2). = (3(3)-5) * (-(2)^2+1) = (9-5)*(-4+1) = 4*(-3)
= -12

1/5g(6) = 1/5(-(6)^2+1) = 1/5(-36+1) = -35/5 = -7

==============================================
For more assistance please visit www.classof1.com.
Classof1 - leading web tutoring and homework help.
Toll free - 1877-252-7763

2007-06-12 21:16:29 · answer #6 · answered by Anonymous · 0 0

-12

2007-06-12 21:07:47 · answer #7 · answered by || 2 · 0 1

B

2007-06-12 21:07:31 · answer #8 · answered by Anonymous · 0 1

fedest.com, questions and answers